Electric Mobility and Development - World Bank; International Association of Public Transport (World Bank, Washington, DC, 2018)
This paper is a collaboration between the World Bank’s Transport Global Practice, the World Bank’s Energy Sector Management Assistance Program (ESMAP) and the International Association of Public Transport (UITP) to assemble evidence, viewpoints, and analysis on eMobility programs. The objective is to contribute towards helping governments design and implement electric mobility programs that are effective at achieving their intended development aims across climate, economic, fiscal, technical, institutional, and policy dimensions. There is a clear global interest in electric mobility and demand for sharing experiences between countries of all income levels.